BS26 Generation of a tissue engineered conduit from human saphenous vein and porcine blood outgrowth endothelial cells. (May 2019) - Bond, Andrew; Sulaiman, Nadiah; Bruno, Vito; Johnson, Jason; George, Sarah; Ascione, Raimondo
Abstract : Introduction: Coronary artery bypass grafting (CABG) primarily uses autologous human saphenous vein (hSV), despite autologous arteries having better patency rates. However, a lack of arteries, and presence of disease in those which are available, has led to the need to develop alternative tissue engineered conduits. Here we aim to arterialise a vein, by re-seeding a decellularised hSV (DhSV) with arterial-like endothelial cells (EC), which will ultimately prevent early thrombosis and improve late graft patency. Methods: Blood outgrowth EC (BOEC) isolated from 350 ml pig blood were expanded for further use. BOEC were subjected to immunocytochemistry (ICC) for EC markers CD31, vWF, VE-Cadherin, and DBA-Lectin, and also vimentin (mesenchymal/fibroblast marker) and CD45 (leukocyte marker). BOEC seeded in plates were exposed to dynamic (D) culture conditions on an orbital shaker (94 hrs) and compared to static (S) culture. EC isolated from pig aorta (PAEC) were used as positive controls. qPCR was performed for CD31, vWF, VE-Cadherin, eNOS, DLL4 (arterial) and NR2F2 (venous). hSV was decellularised using 0.01% SDS. 1 × 106 BOEC were seeded onto DhSV by tying the ends (T) to trap cells luminally, or placing BOEC in the lumen leaving ends untied (UT), before leaving under static (S) or dynamic (D: roller, 1rpm) culture conditions (93 hrs). Seeded DhSV were static cultured for 73 hours, fixed, paraffin wax-embedded and sections subjected to DBA-lectin staining to quantify maximum lumen coverage of BOEC, and anti-CD31 immunohistochemistry. Results: BOEC showed classic EC cobblestone morphology, and ICC staining revealed expression of CD31, DBA-Lectin, vWF, vimentin, VE-Cadherin levels were low and CD45 was not detected. CD31 mRNA levels were comparable in BOEC and PAEC (fold-change (FC) 1.2), while vWF (FC 228.3), VE-cadherin (FC 9.3) and NR2F2 (FC 5.5) mRNAs were increased and eNOS (FC 0.2) and DLL4 (FC 0.1) were decreased in BOEC compared to PAEC. Exposing BOEC to shear stress increased expression of all mRNAs investigated (FC CD31:2.6, vWF:1.8, VE-cadherin:1.4, eNOS:3.3, DLL4:1.4, and NR2F2:3.4) compared to static BOEC. Seeding DhSV resulted in partial re-endothelialisation with greatest lumen coverage found by dynamic seeding with cells tied into lumen (91% coverage) and continued culture resulted in a near complete BOEC layer following (97%). CD31 was still expressed in seeded DhSV. ConclusionS: BOEC isolated from pig blood show expression of EC markers, and vimentin, and are negative for the leukocyte marker CD45. We have shown that it is possible to repopulate a DhSV with BOEC and, under the correct conditions, obtain a functional monolayer around the lumen. This preliminary data shows the translational potential for this approach in generating a tissue engineered saphenous vein, reendothelialised with BOEC from blood that could be used for CABG. Conflict of interest: None